Measurement of Onset of Structural Relaxation in Melt‐Quenched Phase Change Materials. (27th June 2021) - Kersting, Benedikt; Sarwat, Syed Ghazi; Le Gallo, Manuel; Brew, Kevin; Walfort, Sebastian; Saulnier, Nicole; Salinga, Martin; Sebastian, Abu
Abstract: Chalcogenide phase change materials enable non‐volatile, low‐latency storage‐class memory. They are also being explored for new forms of computing such as neuromorphic and in‐memory computing. A key challenge, however, is the temporal drift in the electrical resistance of the amorphous states that encode data. Drift, caused by the spontaneous structural relaxation of the newly recreated melt‐quenched amorphous phase, has consistently been observed to have a logarithmic dependence in time. Here, it is shown that this observation is valid only in a certain observable timescale. Using threshold‐switching voltage as the measured variable, based on temperature‐dependent and short timescale electrical characterization, the onset of drift is experimentally measured. This additional feature of the structural relaxation dynamics serves as a new benchmark to appraise the different classical models to explain drift. Abstract : In phase change memory devices, a nanoscopic amorphous volume of a chalcogenide compound is used to encode information. The onset of structural relaxation of the glassy state is revealed, created with quench rates of 10 10 K s −1 . This additional feature of the relaxation dynamics serves as a new benchmark to appraise different models to explain relaxation and drift in these devices.